2009
DOI: 10.1590/s1413-81232009000100023
|View full text |Cite
|
Sign up to set email alerts
|

Programa de Saúde da Família e Saúde Mental: impasses e desafios na construção da rede

Abstract: Programa de Saúde da Família e Saúde Mental: impasses e desafios na construção da redeThe Family Health Program and Mental Health: difficulties and challenges for building a network

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 1 publication
0
9
0
19
Order By: Relevance
“…A study carried out in Salvador, BA, Brazil concerning how health professionals interpret mental suffering and how they plan and develop their interventions in the FHS, found that some professionals invest a lot of work creating bonds between the community and the health unit and also increase its participation in the resolution of problems at the family health level (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out in Salvador, BA, Brazil concerning how health professionals interpret mental suffering and how they plan and develop their interventions in the FHS, found that some professionals invest a lot of work creating bonds between the community and the health unit and also increase its participation in the resolution of problems at the family health level (6) .…”
Section: Introductionmentioning
confidence: 99%
“…O Modelo Psicossocial, trazido pela Reforma, propõe que fatores políticos, biopsíquicos e sócio-culturais sejam tomados como determinantes das doenças. Dessa forma, "as terapias sairiam do escopo medicamentoso exclusivo, ou preponderante, e o sujeito ganharia destaque como participante principal no tratamento, sendo a família e, eventualmente, um grupo mais ampliado, também incluídos como agentes fundamentais do cuidado" (17).…”
Section: Resultados E Discussões O Contexto Da Estratégia Do Acompanhunclassified
“…The interviews were recorded, transcribed and analysed by thematic content analysis 24 . In this procedure, the content of the interviews was compared seeking Fear, anguish and anxiety are common reactions of primary care professionals in dealing with mental health issues 26,27 . There is a fear of unpredictable behaviours, including violent behaviour, at the same time as professionals perceive themselves as having few resources to help, generating a sense of unpreparedness and fear.…”
Section: Methodsmentioning
confidence: 99%